2018
DOI: 10.3389/fvets.2018.00149
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Modulates Luteinizing Hormone Release and Ovarian Follicular Dynamics in Pre-pubertal and Adult Murrah Buffaloes

Abstract: Kisspeptin is a neuropeptide that governs the reproductive axis upstream to GnRH. We wanted to study whether kisspeptin modulates plasma LH and FSH levels and ovarian follicular dynamics in buffaloes and whether kisspeptin can be used for fixed time artificial insemination (FTAI). We carried out these studies in comparison with buserelin, a potent GnRH agonist. Kisspeptin dose-dependently increased plasma LH levels. However, the kisspeptin-induced increase in LH was short-lived as the peak reached in 15–30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
(31 reference statements)
1
10
0
1
Order By: Relevance
“…Though most of the studies have emphasized the anti-angiogenic effect of kisspeptin, especially during tumour growth, a few studies have shown that kisspeptin increases migration and proliferation of endothelial cells, the components of angiogenesis (Golzar and Javanmard, 2015). Facilitation by kisspeptin of ovarian follicular growth has been observed in vivo in livestock species (Pottapenjera et al, 2018). The current study supports the in vivo observation and further suggests a direct action of kisspeptin on ovaries rather than indirect effects via release of gonadotropins.…”
Section: Discussionsupporting
confidence: 81%
“…Though most of the studies have emphasized the anti-angiogenic effect of kisspeptin, especially during tumour growth, a few studies have shown that kisspeptin increases migration and proliferation of endothelial cells, the components of angiogenesis (Golzar and Javanmard, 2015). Facilitation by kisspeptin of ovarian follicular growth has been observed in vivo in livestock species (Pottapenjera et al, 2018). The current study supports the in vivo observation and further suggests a direct action of kisspeptin on ovaries rather than indirect effects via release of gonadotropins.…”
Section: Discussionsupporting
confidence: 81%
“…The LH surge is increased due to the administration of Kp but no longer sustains the peak and the Kp is enhance the follicular growth and a follicular number of the Murrah buffalos up on the age of animals (Pottapenjera et al, 2018) [17] . The Kp and Kp1r expression can change the follicular development stage of the estrous cycle and expression is higher in the case of cyclic compared to the acyclic buffaloes.…”
Section: Buffalomentioning
confidence: 99%
“…Exogenous injection of Kp in different modes can enhance the release of gonadotrophin of LH in a number of species. The kp neurons act on the GnRH and activate for secretion of gonadotrophin in Mice (Messager et al, 2005) [7] , Gilts (Lents et al, 2008) [8] , Mare (Wilborn et al, 2008) [10,34] , Cattle (Ezzat et al, 2010) [9,42] , Goats (SAITO et al, 2011) [11] , Men (George et al, 2011) [12] , Women (Dhillo et al, 2007; Jayasena et al, 2014) [14,15] , Ewes (Wang et al, 2012) [13] , Dogs (Albers-Wolthers et al, 2014) [16] , Buffalo (Pottapenjera et al, 2018) [17] . The kp and its receptor are expressed in the ovaries of many species (Roman et al, 2012;Hu et al, 2017;Terao et al, 2004;Iwata et al, 2017) [18,19,20,21] , mainly expressed in granulosa cells of rats and predominantly expressed in mice oocytes (Chakravarthi et al, 2018) [22] .…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding led to the suggestion that KISS1 agonists may have potential in the management of puberty in livestock. In this regard, KISS-10 induced gonadotropin secretion and influenced ovarian function in prepubertal buffalo [ 183 ], cattle [ 180 ], sheep [ 186 , 187 ], and pigs [ 177 , 188 ]. KISS-10 also induced gonadotropin secretion and ovulation in seasonally anestrous ewes [ 189 , 190 ] and synchronized ovulation in goats [ 79 ].…”
Section: Application Of Kiss1 In Assisted Reproduction In Livestockmentioning
confidence: 99%